Peran dan Perkembangan Ilustrasi - Joneta Witabora (Humaniora, 2012)
Humans are social creature, therefore the need to communicate is the foundation of human nature. Communication has a variety of ways and forms, one of which is to communicate visually. Visual communication is an early form of human expression of the need to interact, and is the origin of the fine arts. The illustration is one of the disciplines that have long existence. The development of the illustration cannot be separated from human history. The world of social and cultural, science and technology has become home to the world of illustration to flourish. Article presents  the existence of illustrations, mapping the functions and the roles of illustration provide a more in-depth knowledge in the use of visual imagery.